KONSTITUSIONALITAS PERATURAN PEMERINTAH PENGGANTI UNDANG - UNDANG NOMOR 1 TAHUN 2014 TENTANG PEMILIHAN GUBERNUR, BUPATI DAN WALIKOTA - Abdul Kapi; Emilda Firdaus; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Government Regulation in Lieu of Law - Law (PERPPU) is a rule of law issued by the President. That in the constitution and the Law - Law No. 12 of 2011 Concerning the Establishment Regulations - Invitation, and also set out in the Constitutional Court decision, it is given the authority by to President to publish, without the approval of the House of Representatives first. Even after the President issued Government Regulation in Lieu of Law - Law must be submitted to Parliament for discussion at its next session. In the issuance of Government Regulation in Lieu of Law - Law countries are in a state of emergency or urgency that forces, for the government in this regard the President as the key policy-makers, it must act quickly to overcome all permasalahanya. In the constitution in the issuance of Government Regulation in Lieu of Law - Law, what if guided by legal rules that govern them, then it is considered the constitutionality of the top publishers.Or in accordance with the constitution or rules of law. In the case of the issuance of Government Regulation in Lieu of Law - Law No. 1 of 2014 About Election of governors, regents and mayors, in which regulated the election mechanism Governors, Regents and Mayors conducted directly by the people, and in the Act - Act before that Act - Law Number 22 Year 2014 About Election governors, regents and mayors, the Act - This Act also regulates the election mechanism Governors, Regents and Mayors conducted a representative, or by the Legislative Council, Law - Law this is rejected by society in general, so diterbitkanya Government Regulation in Lieu of Law - Act to reinstate the right of people to choose or determine the choice of the head region.Keywords: constitutionality - in lieu of government regulation - legislation